2006
DOI: 10.1598/rrq.41.2.5
|View full text |Cite
|
Sign up to set email alerts
|

Building on theoretical principles gleaned from Reading Recovery to inform classroom practice

Abstract: The authors, both of whom are outside the network of scholars and practitioners typically associated with Reading Recovery, describe the instructional and teacher professional development components of the program and review related research. They then explore the theory and instructional assumptions on which RR is based, positing that both have implications for effective classroom instruction. In fact, they argue that the theory and assumptions of RR can be considered as core to good literacy instruction for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Whereas the use of Reading Recovery has declined in schools (Cox & Hopkins, ), the reflective behind‐the‐glass routine remains a fruitful structure for PSTs and inservice teachers to inspect and flexibly alter their teaching practice. Behind‐the‐glass teaching has been translated to teacher education in literacy clinic settings with school–university partnerships (Dozier, Johnston, & Rogers, ), and the transfer of learning to classrooms has been documented as successful in several studies (Carr, ; Deeney et al., ; Dozier & Rutten, ).…”
Section: Teaching Behind the Glassmentioning
confidence: 99%
“…Whereas the use of Reading Recovery has declined in schools (Cox & Hopkins, ), the reflective behind‐the‐glass routine remains a fruitful structure for PSTs and inservice teachers to inspect and flexibly alter their teaching practice. Behind‐the‐glass teaching has been translated to teacher education in literacy clinic settings with school–university partnerships (Dozier, Johnston, & Rogers, ), and the transfer of learning to classrooms has been documented as successful in several studies (Carr, ; Deeney et al., ; Dozier & Rutten, ).…”
Section: Teaching Behind the Glassmentioning
confidence: 99%
“…Reynolds and Wheldall (2007) reviewed research on reading recovery and concluded that the system of reading assessment provided 'an excellent model in demonstrating how to plan, promote, and implement intervention across an educational system' (p. 218). Cox and Hopkins (2006) argue strongly that use of reading recovery becomes an important focus for teacher educators in order to provide new graduates with essential skills required because children have different preschool, life and social experiences, noting that no literacy program or set of instructional THE AUSTRALIAN JOURNAL OF INDIGENOUS EDUCATION procedures will meet the needs of every child. Reading recovery is a means that teachers can use to identify student needs on key areas of literacy development.…”
Section: Improving Literacy Outcomesmentioning
confidence: 99%
“…Reading recovery is also noted as a systematic and comprehensive program of professional development. Cox and Hopkins (2006) present five measures of reading achievement that the program of reading recovery targets. The fifth of these measures involves text reading, which is accompanied by running records used to determine the level at which the student can read with 90% or greater accuracy.…”
Section: Improving Literacy Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, for the teaching of reading to be effective, the teacher's knowledge of the teaching process has to be applied in the teaching of reading. Cox & Hopkins (2006), after reviewing Reading Recovering, an internationally recognized program for lowachieving first grade pupils in reading, conclude that the key to reading lies in the hands of professional development. They, therefore, advise that undergraduate teachers should be given extensive experience during training to observe emergent and developing readers and writers in real primary classrooms.…”
Section: Professional Development Of Teachersmentioning
confidence: 99%